OBSERVATION ON THE FISHERY AND BIOLOGY OF PENAEID PRAWNS FROM GODAVARI ESTUARY - Devi, S Lalitha (Indian Journal of Fisheries, 2011)
The Godavari estuarine system of Andhra Pradesh covering an area of 330 sq. km, supports a lucrative prawn fishery. Subrahmanyam (1965, 1967, 1973) and Ganapati and Subrahmanyam (1966) made preliminary study of the prawn fishery of this area. Rao (1975) dealt with the prawn fishery of the Kakinada backwaters based on the data collected from Boddu Venkatayapalem during 1968-73.